PENGELOLAAN PERMINTAAN DAN KAPASITAS PRODUKSI PADA UMKM “OSH SALON” DI KOTA BATAM - Ivan Jones; Lusiana Lusiana; Moderin Moderin; Fenny Fenny (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
In this day and age, humans are increasingly busy with their work so they don't have time to care for and beautify themselves. This OSH Salon really helps people who are very busy but still want to look beautiful because customers just sit quietly and relax and then the salon will pamper and beautify you. This can also help those of you who are busy and stressed about work to relax for a moment. The research method we use is qualitative because this method emphasizes the depth of the data to be studied by us so that it is more accurate and easier to research. Based on the results of the data we got in 2019 before the pandemic, this MSME served around 70 customers every week, while in 2020 it served around 58 customers every week, and in 2021 there will be an increase again around 65 customers every week. The conclusion we can give is that doing treatments at the salon is very helpful for those of us who are busy and can save time compared to doing treatments at home. Salon is also a place for us to relax ourselves who may be quite stressed about our work.